Information Sharing and Market Performance of Micro, Small and Medium Enterprises in Wakiso District, Uganda - Henry Stanley Mbowa; Marus Eton; Alice Ngele Mwazuna (Journal of Digital Business and Marketing, 2026)
Purpose: The study examined the influence of information sharing on the market performance of selected manufacturing SMEs in Wakiso district. Research Methodology: The study used a cross-sectional design with a convergent/concurrent mixed-methods approach for efficient data collection. A sample of 340 respondents was selected from 2,279 employees and proprietors using Yamane. Key informants were purposively chosen, while employees were randomly selected. Data was collected through interviews and questionnaires, with a pilot test conducted in Wakiso town council (10% sample size) showing reliability (? = 0.801) and validity (0.714). SPSS v.16.0, JASP, and NVivo were used for data analysis. Results: Information sharing had a positive but non-significant effect on the market performance of manufacturing SMEs in Wakiso District (? = 0.679; p > 0.565). Qualitatively, results revealed that information sharing plays a central role in influencing market performance. Conclusions: It is hard for the SMEs to rely on INS to improve market performance. So, SMEs must ensure that the information they provide to their customers is reliable, accurate, timely and accessible. Limitations: The study was limited to MSMEs under carpentry, metal fabrication, and concrete block in Naberu, Kyengera, and Kasangati, which limits the representation of the entire sector, especially in other districts in Uganda. Contributions: The need for MSMEs to equip managers and employees with competences in information preparation and sharing in a timely and appropriate manner customers, and results reinforce the central role of information sharing on market performance.